2007
DOI: 10.1002/path.2172
|View full text |Cite
|
Sign up to set email alerts
|

The α1 subunit of the sodium pump could represent a novel target to combat non‐small cell lung cancers

Abstract: With an overall 5 year survival rate as low as 15% for non-small cell lung cancer (NSCLC), even with surgical intervention and the use of newer molecules in adjuvant chemotherapy, there is an urgent need for new biological targets and associated novel anti-cancer agents. The present study was undertaken to evaluate the potential of the Na(+)/K(+)-ATPase alpha1 subunit as a novel target in NSCLC and revealed that alpha1 expression is markedly higher in a significant proportion of NSCLC clinical samples compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
163
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 44 publications
16
163
0
Order By: Relevance
“…Additionally, the rodent α1 isoform is almost 1,000 times less sensitive to cardiac glycosides than that in the human due to a double mutation in the first extracellular loop (18). After the assessment of adenocarcinomas and squamous cell carcinoma tissues from 59 patients with lung cancer, Mijatovic et al suggested that the α1 isoform of Na,K-ATPase may be a useful target for cardiac glycosides in the treatment of non-small cell lung cancer cells (34). They reported that cardiac glycosides such as ouabain, digixon, and UNBS1450 showed the strongest inhibition of the rat Na,K-ATPase α3β1 isoform followed by α2β1 and α1β1 isoforms growing in sf9-insect cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rodent α1 isoform is almost 1,000 times less sensitive to cardiac glycosides than that in the human due to a double mutation in the first extracellular loop (18). After the assessment of adenocarcinomas and squamous cell carcinoma tissues from 59 patients with lung cancer, Mijatovic et al suggested that the α1 isoform of Na,K-ATPase may be a useful target for cardiac glycosides in the treatment of non-small cell lung cancer cells (34). They reported that cardiac glycosides such as ouabain, digixon, and UNBS1450 showed the strongest inhibition of the rat Na,K-ATPase α3β1 isoform followed by α2β1 and α1β1 isoforms growing in sf9-insect cells.…”
Section: Discussionmentioning
confidence: 99%
“…44) However, it seems that the α1 isoform plays a primary role in Na + / K + -ATPase and is more abundant than the other α isoforms in A549 cells, as siRNA targeting the α1 isoform markedly impaired the proliferation and migration of A549 cells for 6 d. 44) We have found that knockdown of Na It has been reported that ouabain and ouabagenin inhibit the α1β1, α2β1, and α3β1 complexes of human recombinant Na + /K + -ATPase with similar potency, although ouabagenin shows weaker inhibitory activity than ouabain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the investigation of bufadienolides have indicated that RB is a type of biologically active molecule with a wide variety of physiologic and pharmacological functions (Mijatovic et al, 2007;Newman et al, 2008). The previous studies reported that the cytotoxic and cardiotoxic action of bufadienolides varied greatly and the substituted groups of steroid skeletons could significantly influence these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in recent years indicate that resibufogenin possesses significant pharmacological and toxicological effects, including cardiotonic, anesthetic, antitumor, and cardiotoxic effects. Furthermore, both preclinical and clinical studies show that RB and its analogs possess the skeletons of bufadienolide are potent anticancer agents (Mijatovic et al, 2007;Newman et al, 2008). It has been reported that RB exhibits strong cytotoxic activities against human myeloid leukemia, prostate cancer, and human hepatoma cells, with IC 50 values of approximately 10-50 nM (Kamano et al, 1998).…”
Section: Introductionmentioning
confidence: 99%